PENAMBAHAN RAGI TERHADAP MULTIPLIKASI SUBKULTUR TUNAS MANGGIS (Garcinia mangostana L.) SECARA IN VITRO - Erma Safitri, Revina Rizqidia; Wulandari, Reine Suci; Darwati, Herlina (Universitas Tanjungpura, 2013)
Garcinia mangostana L. is a species tropical forest that has many benefit. The benefitmangosteen for human life makes it worth as commodity in International market. This aimed to knowing the influence of addition some yeast concentration for bud multiplication of mangosteen and to getting the best yeast concentration for bud multiplication of mangosteen. The research took place in Sylviculture Laboratory at Tanjungpura University for 2 month. The data analyzed to usecompletely randomized design (CRDwith analysis of variance and followed HSD test. There are five treatments given those are R0= Control 0%, R1 = addition yeast with concentration 8%, R2 = addition yeast with concentration 10%, R3 = addition yeast with concentration 12% and R4 = addition yeast with concentration 14% with 6 repplications so there are 30 explants. For the whole, the parameters observedwere the first times callus and sproud appear, the counts of explants had callus, sproud,browning or constant and the percentation of explants growth. HSD showed thatthe treatments has significantlyinfluence the growth of mangosteen explants. In this study the best result is R1 = addition yeast with concentration 8% where the number of shoots produced as many as 16 buds. Base on it, yeast with concentration 8% give a good influence for the mangosteen explants in vitro. Keywords : Garcinia mangostana., Yeast, Multiplication and Subculture.